LIMINAL SPACE IN WILLIAM BLAKE'S POETRY - Olasode, Chikodi Adeola (UC Journal: ELT, Linguistics and Literature Journal, 2025)
“Thresholds" between different states of consciousness, states of being, or fully cognitive and perceptive states are the essence of many poems by William Blake. This paper discusses how liminality is used by Blake to break limits and express the experience of change. Based on the close readings of the selected examples from Blake’s opus—‘Songs of Innocence and of Experience’—as well as his prophetic books, it is possible to define certain characteristics of the liminal space in his work. The liminal exploration of Blake's poetry possesses the quality of traversing those boundaries and questioning the societal conditions surrounding the event or, at the very least, taking the revisit of innocence by the experience into a different space designated for imagining further with respect to human existence. It should also be noted that there is a duality of the body and a duality of the spirit in Blake's works; they are Blake's pronouncements of a totality both outside the physical and the spiritual.  Through his questioning of set norms, Blake empowers readers to reexamine their understanding of morality, spirituality, and identity and encourages their reincorporation into actual change.